Szterling czy euro: implikacje polityczne - Kowalska, Magdalena Maria (Sterling or Euro: Political Implications, 2008)
The article presents costs and benefits resulting from possible keeping the pound (or introducing the euro) as a currency of the United Kingdom of Great Britain and Northern Ireland. The article touches upon the political and social aspects of the issue. The highlights are: perceiving the national currency as a sovereignty symbol, British vision of Europe and the UK-USA relations as well as the UK participation in the past and future process of integration which takes place in Europe. The last part of the paper presents recent research on negative attitude of British nation towards common currency and the statement that the debate on whether to join the euro zone or not, is in fact a debate on the future of the European Union, which the United Kingdom is willing to accept.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 68-79